Book Reviews. Issue 1 (1st April 2013) - Madhavan, Arya; Nair, Sreenath
My Tears, My Dreams (trans. Sindhu V. Nair), V. T. Bhattathirippad (2013) New Delhi: Oxford University Press, xxxvi+112 pp., h/bk, Rs. 295.00, ISBN: 0198089627Critical Essays on British South Asian Theatre, Graham Ley and Sarah Dadswell (eds) (2012) Exeter: Exeter University Press, x+276 pp., p/bk, ISBN: 9780859898355. £25.00